2012
DOI: 10.1093/annhyg/mes081
|View full text |Cite
|
Sign up to set email alerts
|

Application and Assessment of a Regular Environmental Monitoring of the Antineoplastic Drug Contamination Level in Pharmacies - The MEWIP Project

Abstract: A large-scale study was carried out in order to determine the contamination level of antineoplastic drugs in pharmacies and to investigate the suitability and effects of wipe sample monitoring at regular intervals. A specific study design was developed. The 130 participating pharmacies were divided into a study and a control group, carrying out five and two wipe sampling cycles, respectively. The work practice was analyzed using questionnaires to identify factors that influence the contamination level. From 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 19 publications
7
47
1
Order By: Relevance
“…USP Chapter <797> recommends an ‘action level’ of 1.0 ng/cm 2 for cyclophosphamide, but a recommendation to keep values as low as 0.1 ng/cm 2 would seem to be a reasonably achievable goal. (46,56) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…USP Chapter <797> recommends an ‘action level’ of 1.0 ng/cm 2 for cyclophosphamide, but a recommendation to keep values as low as 0.1 ng/cm 2 would seem to be a reasonably achievable goal. (46,56) …”
Section: Discussionmentioning
confidence: 99%
“…Based on their observation, contamination values above the 75 th percentile were considered high and that handling procedures needed to be optimized. In another German report, Kiffmeyer et al (46) recommended the use of the 90 th percentile and suggested a guidance value of 0.1 ng/cm 2 based on their findings for 5-fluorouracil contamination. However, such an approach requires a large amount of wipe sampling data which is not available in the U.S and suggested values would not be based on a health outcome.…”
Section: Methodsmentioning
confidence: 99%
“…For sampling we chose a day regarded as »normal« by the staff in terms of the number of treatments. Samples from the working and other surfaces were taken with wipes (24).…”
Section: Methodsmentioning
confidence: 99%
“…The risk of exposure is not limited to healthcare workers who prepare (pharmacists and pharmacy technicians) or administer (nurses) cytotoxic agents. Anyone in touch with contaminated air or objects or even patient excreta is at risk (12,(22)(23)(24)(25)(26). One Dutch study (25) identified home care, nursing homes, and laundry facilities as non-hospital occupational settings with higher exposure, which were all related to the care of cancer patients.…”
mentioning
confidence: 99%
“…These workers include shipping and receiving personnel, pharmacists and pharmacy technicians, nursing personnel, and environmental services personnel (20). Workers employed in the synthesis and production of these products and staff involved in cleaning, transport, and disposal of hazardous drugs or contaminated material may all face health risks (20,36,(84)(85)(86). A study done by Meijster and colleagues (84) discussed the most important occupational settings outside hospitals in the Netherlands, where exposure to antineoplastic can also occur.…”
Section: Occupational Exposure To Antineoplastic Drugsmentioning
confidence: 99%